Anti-inflammatory and Anti-arthritic Properties of Mucuna gigantea Plant Extracts: Establishing by Molecular Docking Study - Kumar, Satish; Srivastava, Pratima; Mujwar, Somdutt; Gauttam, Vinod; Gupta, Sumeet (Current Computer - Aided Drug Design, 2025)
<span class=
Keywords: TNFα